If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 6) = 2x Reorder the terms: 6(6 + x) = 2x (6 * 6 + x * 6) = 2x (36 + 6x) = 2x Solving 36 + 6x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 36 + 6x + -2x = 2x + -2x Combine like terms: 6x + -2x = 4x 36 + 4x = 2x + -2x Combine like terms: 2x + -2x = 0 36 + 4x = 0 Add '-36' to each side of the equation. 36 + -36 + 4x = 0 + -36 Combine like terms: 36 + -36 = 0 0 + 4x = 0 + -36 4x = 0 + -36 Combine like terms: 0 + -36 = -36 4x = -36 Divide each side by '4'. x = -9 Simplifying x = -9
| 6x-30-4=4x-3x+14 | | -4x+3y=-20 | | 3(x-7)+4(x+5)=5x+5 | | 3(x-4)+2=x-26 | | 8x^2-16x+12=7 | | 4/6x-7/9=1 | | 4m-2m+4m-5m=17 | | H(t)=-12t+6+20 | | x-7+2x+x+13=180 | | 1/2x-14=-18 | | 1/9- | | 1.5y/2y-4.5 | | 63=9x+9 | | 2(x+4)=33-3x | | 9r-9r+5r+r-2=10 | | 2x+2z= | | 15(14x+9)=-8(x-3) | | -7x+10=5x-46 | | 2k+12=-5 | | 20(-10x+2)=15(x-5) | | 9y^3-39y^2-30y= | | 3/4y=47/8 | | -7+10=5x-46 | | x^2-23x-240=0 | | -6x+12y+3z=-6 | | 8d+4c+d-c= | | 2(-15x-4)=14(x+4) | | 11/32=8/x | | 10w-w-6w=9 | | 4b+8=6b+4 | | 1+8x=3(23x+38)-x | | (-1-X)/-X=0 |